Economic Security at the Pivot of National Security: Foresight into Nepal’s Headway - Adhikari, Roshan (Unity Journal, 2025)
To what extent does a nation's economic security drive its holistic security framework? The existing literature on national security highly concentrates on conventional military security, with the triviality of other dimensions of national security failing to gain adequate foreground in the academic debate. Traditionally, the economic dimension of national security was associated solely with defence spending, demonstrating the defensive orientation. Meanwhile, the economic power was just there to ensure the conventional security approach of militarization. While observing the definition of security from a broader vantage point, the intricate and complex interplay between national security and the economy can be underscored. Against this backdrop, this paper attempts to demonstrate how the perspective of national security has evolved to incorporate the economic dimension of national power and security. The objective of this paper is to unfold the ever-growing significance of economic security and portray it as a prerequisite to other forms of security, including military security. Thus, this article systematically understudies the relationship between economics and security, particularly in the case of Nepal, while positioning and forecasting Nepal's economic security and recommending actionable measures. The qualitative research approach, employing secondary data from academic books, journal articles, research reports, working papers, and newspaper articles, examines how a robust economy is crucial for sustaining and leveraging other national power elements, with military prowess no exception. Methodologically, the research study stresses the cases of advanced economies and the poorest economies globally through a nomothetic explanation to oversee how their economic growth leads to advancement in military capability and holistic national security, gaining a positive momentum through a causative portrayal. The study finds that Nepal faces significant economic insecurity due to the debt crisis, reliance on aid, imports, remittances, capital deficiency, and underdeveloped sectors. To enhance economic security and safeguard national security, Nepal should focus on managing interdependence, leveraging its geostrategic position, and prioritizing economic diplomacy and capital investment guided by effective leadership.